Integrated Design Analysis and Proposition of Train Control System - GENG Hongliang; ZHANG Chao (机车电传动)
The architecture of the CTCS-3 train control system was described, and some problems or difficulties which were generated by the system individual design were introduced. After that, some integrated designs were presented, which could achieve many advantages, such as strengthening the system functions, improving the performances, and simplifying the maintenance, providing strong basis for train control system further improvement.